Commercialization of smallholders: Does market orientation translate into market participation? - Gebremedhin, Berhanu; Jaleta, Moti (International Livestock Research Institute, 2010)
The literature on commercial transformation of smallholders make little distinction between market orientation (production decision based on market signals) and market participation (sale of output). This paper analyses the determinants of market orientation and market participation in Ethiopia separately and examines if market orientation translates into market participation. Empirical results show that market orientation translates strongly into market participation. The key implication of this study is that policy, technological, organizational and institutional interventions aimed at promoting commercial transformation of subsistence agriculture should follow two-pronged approach: improving market orientation of smallholders at production level, and facilitating market entry and participation of households in output and input markets. Focusing on either may not be as effective in achieving the transformation.